Development, validity and reliability of questionnaire for assessing nurses’ knowledge, attitude and practice towards disaster management - Ahayalimudin, Nurul'ain; Ismail, Aniza; Mohd Saiboon, Ismail (2013)
Background: Recently, world have been stunned by a series of unpleasant event such as earthquakes, tsunami, hurricane and it occurs more frequent. Many people have been affected, loss of human life and properties, and expose inhabitants to the short-term and long-term impact of the disaster. In this situation, nurses play crucial role in managing disaster victims,yet they receive petite training. As a caregiver, nurses who are working in hospital-based and community-based should be incorporated in rendering care to obtain maximum outcomes. However, up to day, there is a lack of validated measures to assess the extent of the problem.The purpose of this study tells what person au fait is, what they believe and how they act, and identification of factors associated, thus it will increase awareness among nurses towards disaster management. Methods / Design: This study had developed such questionnaire with a total of 41-items of closed-ended questions and has been analyzed by using PASW statistic 18. It was divided into three (3) sections which are section on knowledge, attitude and practice. The questionnaire was developed and pretested to two groups which consist of 22 nurses who work in Department of Emergency Medicine and Primary Care Centre of Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Reliability test has been carried out and Cronbach’s alpha was computed at 0.83 for knowledge, 0.66 for attitude and 0.78 for practice. After executed the test, there were two questions from attitude section has been removed, however, there is no major changes on the properties of the tool. Minor changes were made based on the verbatim and written comments from respondents and it remains the same meaning. The revised tool was utilized and further tested in a large population. Discussion: Developing a questionnaire to assess knowledge, attitude and practice of nurses would allow investigating their awareness on disaster management. The end results shall contribute to the understanding of disaster management in Malaysia in terms of emergency and public health response among nurses. Identification of factors eventually favouring nurses’ participation in disaster management, thus, will lead to the development and establishment of disaster nursing disciplines in Malaysia.